Phase 1 Trial With the Cell-Based Immune Primer Ilixadencel, Alone, and Combined With Sorafenib, in Advanced Hepatocellular Carcinoma - Rizell, Magnus; Sternby Eilard, Malin; Andersson, Mats; Andersson, Bengt; Karlsson-Parra, Alex; Suenaert, Peter (Frontiers in Oncology, 2019)
Several lines of evidence support immunotherapy in hepatocellular carcinoma (HCC). We have shown that intratumoral injections of the immune primer ilixadencel (pro-inflammatory allogeneic dendritic cells) are safe in renal-cell carcinoma. Here, we assessed ilixadencel as a single agent and combined with sorafenib in advanced HCC. Of 17 HCC patients enrolled, twelve patients received ilixadencel at the dose of 10 x 10e6 cells (six as monotherapy and six in combination with sorafenib), and 5 received ilixadencel at the dose of 20 x 10e6 cells as monotherapy. The primary objective was to evaluate tolerability. All patients had at least one adverse event, with 30% of such events considered as treatment-related, with one single treatment-related grade 3 event. The most common toxicity was grade 1 and 2 fever and chills. Eleven of 15 evaluable patients (73%) showed increased frequency of tumor-specific CD8+ T cells in peripheral blood. Overall one patient had a partial response (with ilixadencel as monotherapy), and five had stable disease as overall best response per mRECIST. The median time to progression was 5.5 months, and overall survival ranged from 1.6 to 21.4 months. Our study confirms the safety of ilixadencel as single agent or in combination with sorafenib and indicates tumor-specific immunological responses in advanced HCC.